DESIGN OF HIGH PERFORMANCE MULTIPLIERLESS LINEAR PHASE FINITE IMPULSE RESPONSE FILTERS - A, APARNA; T, VIGNESWARAN (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This research work proposes the finite impulse response (FIR) filters design using distributed arithmetic architecture optimized for field programmable gate array. To implement computationally efficient, low power, high-speed FIR filter a two-dimensional fully pipelined structure is used. The FIR filter is dynamically reconfigured to realize low pass and high pass filter by changing the filter coefficients. The FIR filter is most fundamental components in digital signal processing for high-speed application. The aim of this research work is to design multiplier-less FIR filter for the requirements of low power and high speed various embedded applications.